Safety of intraocular anti-VEGF antibody treatment under in vitro HTLV-1 infection - Zong, Yuan; Kamoi, Koju; Kurozumi-Karube, Hisako; Zhang, Jing; Yang, Mingming; Ohno-Matsui, Kyoko (Frontiers in Immunology, 2023)
HTLV-1 (human T-cell lymphotropic virus type 1) is a retrovirus that infects approximately 20 million people worldwide. Many diseases are caused by this virus, including HTLV-1–associated myelopathy, adult T-cell leukemia, and HTLV-1 uveitis. Intraocular anti–vascular endothelial growth factor (VEGF) antibody injection has been widely used in ophthalmology, and it is reportedly effective against age-related macular degeneration, complications of diabetic retinopathy, and retinal vein occlusions. HTLV-1 mimics VEGF165, the predominant isoform of VEGF, to recruit neuropilin-1 and heparan sulfate proteoglycans. VEGF165 is also a selective competitor of HTLV-1 entry. Here, we investigated the effects of an anti-VEGF antibody on ocular status under conditions of HTLV-1 infection in vitro. We used MT2 and TL-Om1 cells as HTLV-1–infected cells and Jurkat cells as controls. Primary human retinal pigment epithelial cells (HRPEpiCs) and ARPE-19 HRPEpiCs were used as ocular cells; MT2/TL-Om1/Jurkat cells and HRPEpiCs/ARPE19 cells were co-cultured to simulate the intraocular environment of HTLV-1–infected patients. Aflibercept was administered as an anti-VEGF antibody. To avoid possible T-cell adhesion, we lethally irradiated MT2/TL-Om1/Jurkat cells prior to the experiments. Anti-VEGF antibody treatment had no effect on activated NF-κB production, inflammatory cytokines, chemokines, HTLV-1 proviral load (PVL), or cell counts in the retinal pigment epithelium (RPE) under MT2 co-culture conditions. Under TL-Om1 co-culture conditions, anti-VEGF antibody treatment did not affect the production of activated NF-κB, chemokines, PVL, or cell counts, but production of the inflammatory cytokine IL-6 was increased. In addition, anti-VEGF treatment did not affect PVL in HTLV-1–infected T cells. In conclusion, this preliminary in vitro assessment indicates that intraocular anti-VEGF antibody treatment for HTLV-1 infection does not exacerbate HTLV-1–related inflammation and thus may be safe for use.